Analisis Pengaruh Jumlah Kunjungan Wisatawan,Tingkat Hunian Hotel dan Produk Domestik Regional Bruto terhadap Pendapatan Asli Daerah Kabupaten Gianyar - Dewi, Dima Sitara; Bendesa, I.K.G (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2016)
Local revenues is one indicator that reflects the independence of a region. Local revenue can be used as a source of financing in a wide variety of development programs announced by the government for the region. Gianyar regency is a region that relies on tourism as a source of revenue that contribute substantially to revenue. The purpose of this study was to analyze the effect of the number of tourist arrivals, hotel occupancy rates to local revenues through the acceptance of regional gross domestic product in Gianyar. This research comes from secondary data is data time series starting from 1994 to 2013. The data was collected through documents published by BPS Bali and Gianyar, Gianyar District Revenue Service and the Department of Tourism Gianyar regency. The analysis technique used is the analysis of track or path analysis. Based on the analysis showed that the number of tourist arrivals and gross regional domestic product positive and significant impact directly on revenue Gianyar regency. The number of tourists also indirect effect on revenue through the regional gross domestic product Gianyar regency, while hotel occupancy rates had no significant effect on revenue Gianyar regency, either directly or indirectly.
Keywords: revenue, number of visits tourists, hotel occupancy rates, gross regional domestic product